The Contribution of ‘Urf to the Reform of Islamic Inheritance Law in Indonesia - Ismail, Ismail; Busyro, Busyro; Nofiardi, Nofiardi; Wadi, Fajrul; Alwana, Hanif Aidhil (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2022)
This library research explains the position of â€˜urf as the basis for reforming Islamic law and its contribution to the renewal of inheritance law in Indonesia, using the content analysis method. The result showed that â€˜urf is of higher importance in the renewal of Islamic law and plays a very important role in reforming the inheritance law in Indonesia. Several KHI book II provisions were based on â€˜urf, including the inheritance of adopted children and adoptive parents, Å¼awul ará¸¥Äm, radd, walad, joint property, and substitute heirs. Among the several forms of â€˜urf that have been recognized as Islamic law, â€˜urf of joint property comes from the rich culture and traditions of native Indonesia. Therefore, it has made a valuable contribution to the renewal of Islamic law in Indonesia.